EFFECT OF LAW ENFORCEMENT TO CREATING GOOD GOVERNANCE BASED ON JUSTICE VALUES - Ibnu Affan (UNISSULA, 2021)
The purpose of writing in this article is to find out and analyze the effect of law enforcement in the implementation of good government. The approach method used in normative legal research used in this study uses modern legal concepts. The research result states that the concept of good governance can be realized if governance is organized in a transparent, responsive, participatory manner, obeying legal provisions, oriented to consensus, existence of togetherness, accountability and having a strategic vision. Governance is said to be good if the common goal is carried out well, paying attention to the decision-making process, carrying out regulatory functions, exercising power properly and orderly institutions. Good governance is implemented in the context of democratizing the life of the nation and state. One of the conditions for democratic life is the existence of law enforcement that is just and implemented without a reed perspective. As the first step in creating good governance is to build a sound legal system, both software, hardware, and human resources who run the system.